Group Schema Therapy for Eating Disorders: A Pilot Study - Simpson, Susan G.; Morrow, Emma; Vreeswijk, Michiel v.; Reid, Caroline (Frontiers in Psychology, 2010)
This paper describes the use of Group Schema Therapy for Eating Disorders (ST-E-g) in a case-series of eight participants with chronic eating disorders and high levels of co-morbidity. Treatment was comprised of 20 sessions which included cognitive, experiential and interpersonal strategies, with an emphasis on behavioural change. Specific schema-based strategies focused on bodily felt-sense and body-image, as well as emotional regulation skills. Six attended until end of treatment, two dropped-out at mid-treatment. Eating disorder severity, global schema severity, shame and anxiety levels were reduced between pre- and post therapy, with a large effect size at follow-up. Clinically significant improvement in eating severity was found in four out of six completers. Group completers showed a mean reduction in schema severity of 43% at post-treatment, and 59% at follow-up. By follow-up, all completers had achieved over 60% improvement in schema severity. Self-report feedback suggests that group factors may catalyze the change process in schema therapy by increasing perceptions of support and encouragement to take risks and try out new behaviours, whilst providing a de-stigmatising and de-shaming therapeutic experience.